Ethnic Self-Identification of First-Generation Immigrants - Laura Zimmermann; Klaus F. Zimmermann; Amelie F. Constant (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper uses the concept of ethnic self-identification of immigrants in a twodimensional framework. It acknowledges the fact that attachments to the home and the host country are not necessarily mutually exclusive. There are three possible paths of adjustment from separation at entry, namely the transitions to assimilation, integration and marginalization. We analyze the determinants of ethnic selfidentification in this process using samples of first-generation immigrants for males and females separately, and controlling for pre- and post-migration characteristics. We find strong gender differences and the unimportance of a wide range of premigration characteristics like religion and education at home.
Keywords: Z10; J16; J15; F22; 330; Ethnic self-identification; first-generation immigrants; gender; ethnicity; Internationale Wanderung; Migranten; Ethnische Gruppe; Soziale Integration; Kognition; Geschlecht; Deutschland